DEVELOPMENT OF RICE WAFERS USING PLANT PIGMNETS: A FUTURE PRESPECTIVE FOR NATURAL FOOD COLOURANTS (International Journal of Food and Nutritional Sciences, 2022)
The present study aimed to develop an extruded snack with natural colorants derived from plant pigments to replace the artificial coloured snacks that provides detrimental effects on health. Rice Wafers were developed using rice, sago, beetroot, carrot and mint. The formulated products were evaluated in an organoleptic manner by using hedonic scale rating. Proximate (energy, carbohydrate, protein and fat) and pigmentation (anthocyanin, betalain, beta – carotene, chlorophyll and vit – c) profile were estimated. The frying quality of the Rice Wafers such as oil absorption capacity and expansion on frying were studied. Shelf – life of both dried and fried rice wafers was observed.